2021
DOI: 10.1002/jssc.202100399
|View full text |Cite
|
Sign up to set email alerts
|

Comprehensive feature‐based molecular networking and metabolomics approaches to reveal the differences components in Cinnamomum cassia and Cinnamomum verum

Abstract: Cinnamon was been a widely used plant in medicinal and spices for a long time and has spread all over the world. However, the differences in the components of the bark from Cinnamomum cassia and Cinnamomum verum, the two most common types of cinnamon, have not been thoroughly investigated. In the present experiment, ultra-high-performance liquid chromatography LTQ-Orbitrap Velos Pro hybrid mass spectrometer-based metabolomics coupled with chemometrics and feature-based molecular networking were employed to dra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 32 publications
0
11
0
Order By: Relevance
“…EOs extracted from these two species have very similar chemical profiles and, for this reason, the CC-EO is frequently used to sophisticate the EO extracted from C. zeylanicum EO. In 2021, Xingdong Wu et al identified some secondary metabolites (proanthocyanidins and alkaloids) as the best markers to discriminate between the two cinnamon spices, which are otherwise difficult to distinguish even for most experts [ 40 ]. Both EOs have a strong antimicrobial activity and are characterized by cinnamaldehyde as the major component with the difference that in CC-EO it is present in a higher percentage than in the other-one.…”
Section: Discussionmentioning
confidence: 99%
“…EOs extracted from these two species have very similar chemical profiles and, for this reason, the CC-EO is frequently used to sophisticate the EO extracted from C. zeylanicum EO. In 2021, Xingdong Wu et al identified some secondary metabolites (proanthocyanidins and alkaloids) as the best markers to discriminate between the two cinnamon spices, which are otherwise difficult to distinguish even for most experts [ 40 ]. Both EOs have a strong antimicrobial activity and are characterized by cinnamaldehyde as the major component with the difference that in CC-EO it is present in a higher percentage than in the other-one.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, ergosterol, cadinene, alphaamorphene, alpha-cubebene, hydrocinnamaldehyde, and (E)-cinnamaldehyde were also identified as the major compounds of the C. verum bark essential oil (Ahmed et al, 2020). Wu et al have successfully identified 20 chemical markers for discriminating C. cassia and C. verum (Wu et al, 2021). According to their study, six procyanidin components (cinnamtannin B1, isocinnamtannin B1, procyanidin B2, Cinnamtannin B1+2H, etc.)…”
Section: Phytochemicals In Cinnamon Extractsmentioning
confidence: 99%
“…High‐resolution mass spectrometry (HRMS) has advantages such as high sensitivity, high resolution, and easy coupling with various analytical instruments 14,15 . For example, by coupling HRMS with ultra‐high‐performance liquid chromatography (UHPLC), it is possible to obtain the molecular weight of and structure information on natural products with high throughput 12,16 . Among ion sources, electrospray ionization (ESI) source is currently considered to be the least likely to produce in‐source fragmentation, but the fragmentation within the ESI source is still common due to the molecular properties of certain compounds 17 .…”
Section: Introductionmentioning
confidence: 99%
“…14,15 For example, by coupling HRMS with ultra-high-performance liquid chromatography (UHPLC), it is possible to obtain the molecular weight of and structure information on natural products with high throughput. 12,16 Among ion sources, electrospray ionization (ESI) source is currently considered to be the least likely to produce in-source fragmentation, but the fragmentation within the ESI source is still common due to the molecular properties of certain compounds. 17 The ion fragments produced by in-source fragmentation lead to false positives or even a complete inability to obtain the pseudo-molecular ion peaks of the identified components, which seriously hinder the characterization of compounds prone to in-source fragmentation.…”
Section: Introductionmentioning
confidence: 99%